Investigating Intention to Use Central Bank Digital Currency in Indonesia - Erwanti, Nindita; Prasetyani, Henny (Journal of Information System and Informatics, 2023)
Central Bank Digital Currency (CBDC) is a digital currency issued by a government-controlled central bank of a particular country. Bank Indonesia as the central bank in Indonesia has been trying to develop a CBDC known as digital rupiah. Digital rupiah is expected to complement and perform same function as the fiat money in Indonesia. Research is needed to identify people’s views on the use of CBDCs. This study seeks to understand the factors that influence intention to use CBDC by adapting Technology Acceptance Model. Data were collected through questionnaires from 565 valid respondents. Partial Least Square-Structural Equation Modeling (PLS-SEM) was used to evaluate the proposed model. This study verifies that perceived usefulness, perceived ease of use, hard trust, and soft trust can influence intention to use CBDC in Indonesia, while personal innovativeness is known to influence perceived usefulness and perceived ease of use.